2008
DOI: 10.1111/j.1365-2745.2008.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and exogenous controls of root life span, mortality and nitrogen flux in a longleaf pine forest: root branch order predominates

Abstract: Summary 1.Root life span regulates the quantity and quality of root-derived organic matter transferred to the soil organic matter pool. However, poor understanding of the rates and controls of root life span has hindered the prediction of carbon (C) flow and nutrient cycling dynamics at the ecosystem scale. 2. We examined the effects of root branch order, root diameter, mycorrhizal colonization, season of birth, depth in the soil, nitrogen (N) fertilization and foliage removal on root life span in a longleaf p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
169
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 37 publications
(167 reference statements)
15
169
0
4
Order By: Relevance
“…Stadelmann et al (1998) reported that low N concentration and the high C/N ratio could be attributed to the high mortality and poor development of root system in Festuca rubra seedlings obtained from in-vitro culture. Presence of vital cortical tissue is necessary for successful mycorrhizal colonization (Peterson et al 1999;Brundrett 2002), as colonization of root tissues by arbuscular mycorrhiza is related to the amount of primary cortex, and differences in root anatomy may impact absorptive ability (Guo et al 2008). However, our study did not show such an obvious dependence, as no differences in the number of arbusculae were observed in relation to seed storage temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Stadelmann et al (1998) reported that low N concentration and the high C/N ratio could be attributed to the high mortality and poor development of root system in Festuca rubra seedlings obtained from in-vitro culture. Presence of vital cortical tissue is necessary for successful mycorrhizal colonization (Peterson et al 1999;Brundrett 2002), as colonization of root tissues by arbuscular mycorrhiza is related to the amount of primary cortex, and differences in root anatomy may impact absorptive ability (Guo et al 2008). However, our study did not show such an obvious dependence, as no differences in the number of arbusculae were observed in relation to seed storage temperature.…”
Section: Discussionmentioning
confidence: 99%
“…However, measurements of isotopes in fine roots demonstrated that both the 14 C age (Gaudinski et al, 2001) and the incorporation rate of a continuous 13 C label (Matamala et al, 2003) in fine root C were inconsistent with an annual turnover. The various observations can be reconciled by assuming that fine roots are not a single homogeneous pool (Gaudinski et al, 2010;Guo et al, 2008;Strand et al, 2008;Tierney and Fahey, 2002;Trumbore, 2009). To date, published fine root radiocarbon ( 14 C) data are mostly from forest ecosystems and little is known of how these observations apply to non-forested ecosystems, or a range of forest types (Fröberg, 2012;Gaudinski et al, 2010;Riley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Second, temperatures of smoldering fires could cause significant thermal damage to roots in the adjacent patches of forest floor not directly consumed by smoldering fire. Because roots are a connected network of segments, when structural roots near the tree are killed, all roots downstream are also lost (Guo et al 2008). This indirect fire-caused root mortality may include the death of downstream roots deep into the mineral soil as well.…”
Section: Discussionmentioning
confidence: 99%